Pre-eclampsia: Universal Screening or Universal Prevention for Low and Middle-Income Settings? - De Oliveira, Leandro Gustavo [UNESP]; Debs Diniz, Angelica Lemos; Campos Prado, Caio Antonio de; Da Cunha Filho, Edson Vieira; Pereira De Souza, Francisco Lazaro; Korkes, Henri Augusto; Ramos, Jose Geraldo; Costa, Maria Laura; Correa Junior, Mario Dias; Sass, Nelson; Cavalli, Ricardo De Carvalho; De Almeida Martins-Costa, Sergio Hofmeister; et al. (Federacao Brasileira Soc Ginecologia & Obstetricia-febrasgo, 2021)
Pre-eclampsia (PE) is a severe disorder that affects up to 8% of all pregnancies and represents an important cause of maternal and perinatal morbidity and mortality. The screening of the disease is a subject of studies, but the complexity and uncertainties regarding its etiology make this objective a difficult task. In addition, the costs related to screening protocols, the heterogeneity of the most affected populations and the lack of highly effective prevention methods reduce the potential of current available algorithms for screening. Thus, the National Specialized Commission of Hypertension in Pregnancy of the Brazilian Association of Gynecology and Obstetrics Federation (Febrasgo, in the Portuguese acronym) (NSC Hypertension in Pregnancy of the Febrasgo) considers that there are no screening algorithms to be implemented in the country to date and advocates that Aspirin and calcium should be widely used.
Keywords: preeclampsia; screening; prevention; aspirin; calcium